Penerapan Akuntansi Murabahah Pada Koperasi Konsumen Syariah Politeknik Aceh (KOPMENSYAPA) - Abthahi, Muhammad; Fauziah, Sri Rani; Sara, Fahmi; Nazalia, Roza (Universitas Teuku Umar, 2025)
This study examines murabahah accounting in recognition, measurement, presentation, and disclosure at the Sharia Consumer Cooperative of Aceh Polytechnic (Kopmensyapa) using Financial Accounting Standards Statement (PSAK) 102. This study uses qualitative and descriptive methods. Data collection was carried out by observation, interviews, and documentation from primary and secondary sources. The results of the analysis found that the management of Kopmensyapa's murabahah accounting violated PSAK 102. First, Kopmensyapa's murabahah accounting process violated PSAK 102 because there was no accounting or inventory recording for recognition and measurement. Second, there was no accounting recording for recognition and measurement or murabahah inventory. Second, murabahah receivables were presented at net realizable value, and the pending margin was not deducted (counter-account). Third, the financial statements' disclosure of murabahah receivables does not include a report on the origin and allocation of zakat monies or the source and utilization of charitable contributions